Ambient temperature cross-linking of a sustainable, cardanol-based cyanate ester via synergistic thiol–ene copolymerization. Issue 21 (13th May 2022) - Muldoon, Jake A.; Garrison, Michael D.; Savolainen, Markku A.; Harvey, Benjamin G.
Abstract : A cyanate ester derived from bio-based cardanol was cross-linked at room temperature via synergistic thiol–ene chemistry catalyzed by UV irradiation. Abstract : Cardanol, a low-cost component of cashew nut shell oil, is a phenolic compound with a 15-carbon unsaturated chain in the position meta to the hydroxyl group. This biorenewable substrate was converted to a cyanate ester resin and blended with a trifunctional thiol at different ratios. Irradiation of the blend with UV light (254 nm) facilitated thiol–ene reactions with concomitant cyclotrimerization of the cyanate ester group without additional heating. This novel synergistic approach allowed for cyanate ester cure under ambient conditions, while enhancing the degree of cross-linking. Through this approach, an elastomeric cross-linked network with a T g of −2.4 °C was prepared. This material may have potential applications as a toughener for rigid cyanate esters or self-healing materials that can take advantage of the reversible nature of thiol–ene chemistry.